Safety and efficacy of add-on intra-arterial thrombolysis after intravenous thrombolysis and mechanical thrombectomy in patients with ischemic stroke and cerebral vessel occlusion - Diel, Norma J.; Woelk, Kai Bernhard; Mrochen, Anne; Posner, Oliver; Worm, Andre; Alhaj Omar, Omar; Claudi, Christian; Schramm, Patrick; Struffert, Tobias; Huttner, Hagen B. (Frontiers in Neurology, 2025)
IntroductionFor acute ischemic stroke (AIS) with large vessel occlusion (LVO), the currently established treatment strategy of combined intravenous thrombolysis (IVT) and endovascular thrombectomy (EVT) is not sufficiently effective in all patients. Intra-arterial thrombolysis (IAT) as an adjunct to IVT/EVT may improve outcomes but may also increase the rate of hemorrhagic complications.MethodsThis observational study analyzed data from the Giessen Stroke Registry (GIST; NCT05295862) between May 2022 and June 2024. Patients with AIS and LVO who received both IVT and EVT were included. A subset of patients received additional IAT (triple treatment, TT). Using 1:1 propensity score matching, 33 TT patients were compared with 33 controls who received only IVT + EVT. Primary outcomes were hemorrhagic complications (ECASS classification), and secondary outcomes included reperfusion rates, ASPECTS scores, 7-day mortality, and functional outcomes.ResultsBaseline characteristics were balanced between the TT and the control group. The primary outcome was not significantly different with a rate of hemorrhagic complications of 3/33 (9%) in the TT group and 4/33 (12%) in the control group (OR 0.725, 95% CI 0.149–3.525). Secondary outcomes showed no significant differences with respect to rates of successful reperfusion, ASPECTS scores or 7-day mortality rates between TT and the control group.ConclusionTriple treatment (IVT, EVT, and IAT) did not significantly improve clinical outcomes compared to IVT and EVT alone. However, TT was safe without signs of increased bleeding complications. TT should not be routinely used until further evidence verifies safety and substantiates a possible benefit in specific patient populations.